Effect of wetland degradation on plant community characteristic and aboveground biomass in the lower reaches of the Yellow River - Huang, Yike; Zhang, Mingli; Mao, Zhiwei; Li, Xinyu; Xu, Linjun; Nie, Jialiang; Li, Xiu; Li, Mengxia; Chen, Wenkai; Ding, Junxiang (Frontiers in Plant Science, 2026)
IntroductionWetlands are among the most vital ecosystems on Earth, yet they also face severe degradation risks due to intensifying human activities and climate change. Clarifying the response of wetland plant communities to habitat degradation and its key drivers is therefore essential for the effective conservation, restoration, and management of wetland ecosystems. However, how plant community biomass responds to degradation and the underlying drivers remain poorly understood.MethodsHere, we measured plant community characteristics and soil physicochemical properties along a well-characterized degradation gradient of wetlands in the lower reaches of the Yellow River to determine the drivers of variation in plant community aboveground biomass.ResultsThe results showed that aboveground biomass, community coverage, density, and height of the wetland plant community decreased consistently with intensifying degradation, whereas species diversity showed no significant change. The variation in aboveground biomass was significantly associated with community structural metrics (e.g., coverage, density, height) but not with species diversity. Furthermore, changes in soil nutrient availability rather than water conditions were the dominant environmental factor driving the decline in aboveground biomass with wetland degradation.DiscussionCollectively, these findings underscore the critical role of soil nutrient availability in mediating wetland plant community structure and function under degradation scenarios. This insight is crucial for understanding wetland ecosystem degradation mechanisms and could inform restoration strategies for degraded wetlands.